Gut microbiome stability and resilience: elucidating the response to perturbations in order to modulate gut health. Issue 3 (13th October 2020) - Fassarella, Marina; Blaak, Ellen E; Penders, John; Nauta, Arjen; Smidt, Hauke; Zoetendal, Erwin G
Abstract : The human gut microbiome is a complex ecosystem, densely colonised by thousands of microbial species. It varies among individuals and depends on host genotype and environmental factors, such as diet and antibiotics. In this review, we focus on stability and resilience as essential ecological characteristics of the gut microbiome and its relevance for human health. Microbial diversity, metabolic flexibility, functional redundancy, microbe–microbe and host–microbe interactions seem to be critical for maintaining resilience. The equilibrium of the gut ecosystem can be disrupted by perturbations, such as antibiotic therapy, causing significant decreases in functional richness and microbial diversity as well as impacting metabolic health. As a consequence, unbalanced states or even unhealthy stable states can develop, potentially leading to or supporting diseases. Accordingly, strategies have been developed to manipulate the gut microbiome in order to prevent or revert unhealthy states caused by perturbations, including faecal microbiota transplantation, supplementation with probiotics or non-digestible carbohydrates, and more extensive dietary modifications. Nevertheless, an increasing number of studies has evidenced interindividual variability in extent and direction of response to diet and perturbations, which has been attributed to the unique characteristics of each individual's microbiome. From a clinical, translational perspective, the ability to improve resilience of the gut microbial ecosystem prior to perturbations, or to restore its equilibrium afterwards, would offer significant benefits. To be effective, this therapeutic approach will likely need a personalised or subgroup-based understanding of individual genetics, diet, gut microbiome and other environmental factors that might be involved.